2019
DOI: 10.7759/cureus.6062
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Assess the Factors Affecting Adherence to Exercise in the Indian Population

Abstract: IntroductionAs proven by many previous studies, physical inactivity is associated with many diseases, including heart conditions and cancer. The elimination of physical inactivity helps increase life expectancy and reduce morbidity. Nonadherence to exercise is a common problem faced by many people. The goal of this study was to determine the percentage of people in the Indian population who regularly exercise. We also assessed factors for nonadherence, motivating factors, and the intensity of exercise usually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…On the other hand, this study observed no significant association between recreational runners' education level and their practice toward CSE. In line with this finding, (Shettigar et al, 2019) found that an individual's level of education was not significantly associated with exercise adherence. However, previous studies stated that education level is associated with the level of practice of physical exercise (Tarducci et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, this study observed no significant association between recreational runners' education level and their practice toward CSE. In line with this finding, (Shettigar et al, 2019) found that an individual's level of education was not significantly associated with exercise adherence. However, previous studies stated that education level is associated with the level of practice of physical exercise (Tarducci et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…Various reasons documented in the present study for non-consent or non-adherence to the study protocol were a busy daily schedule on the farm, a change of place, or any medical condition during the tenure such as knee injuries, fractures, pulmonary conditions, stroke, or mortality. Various reasons cited in the literature pertaining to non-adherence to an exercise programme were lack of time due to social, work, or family responsibilities, lack of interest, and being reluctant to change the daily routine (17) , (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Coming to the challenges, “lack of time,” and “lack of motivation” are the most important factors affecting the lack of physical activity in India. 36 These factors might be held responsible for the “staggering” difference between Indian and global levels of physical inactivity. 2 , 33 Understandably, the inability to find time for physical activity is due to the busy work schedule for those in job/business.…”
Section: Relevance To Indiamentioning
confidence: 99%
“…In general, “encouragement from significant others” in the family is the strongest sociocultural determinants of higher levels of physical activity. 37 For Indians, especially girls and women, this determinant is not available to a large extent 36 due to cultural sanctions (this has been depicted in the Bollywood movie “Dangal”). In this context, family-oriented physical activity interventions where parents are invited to encourage and play with children have been proposed for improving physical activity levels in children.…”
Section: Relevance To Indiamentioning
confidence: 99%